Combined effect of slag and clay brick powder on the hydration of blended cement. (13th September 2021) - Zhao, Yasong; Gao, Jianming; Xu, Zhenhai; Li, Shujun; Luo, Xu; Chen, Gaofeng
Highlights: Slag and CBP were used as supplementary materials to prepare blended cement. Slag can accelerate C3 A hydration more dramatically than CBP. CBP consumes more portlandite than slag after 90 d. Blended cement continues to hydrate due to the combined effect of slag and CBP. Abstract: The slag from industrial byproduct and clay brick powder (CBP) from construction waste were used to replace 30% Portland cement for preparing blended cement. This research investigated the hydration heat, hydration products, microstructure and macro-mechanical properties of blended cement to reveal the combined effect of slag and CBP on hydration. The test results indicate that 30% slag and CBP can increase 11.4 ~ 13.7% peak value of C3 S hydration, but the C3 A hydration is more affected by slag than CBP. Meanwhile, the 144-h cumulative heat of blended cement hydration is reduced by 4.1 ~ 21.3% compared to Portland cement. The slag and CBP have an improvement effect on the mechanical strength of mortars before and after 90 d, respectively. The mechanical strength of mortars containing both slag and CBP can develop continuously for a long time and reaches the highest value of 53.5 MPa. The slag can consume more portlandite than CBP before 90 d, the portlandite contents in C7B0 and C7B100 at 90 d are 11.6% and 13.3%, respectively. But after 90 d, the CBP will react with more portlandite for its pozzolanic activity. Some different morphologies of CASH can be observed in blended cement paste due to the variation of Al/Si and Ca + Mg/Al + Si in CASH. It could be concluded the combined effect of slag and CBP will led to a high hydration degree at an early stage and continuous hydration for a long time in blended cement.